2014 Mid-Atlantic Telehealth Resource Center Annual Summit - Wibberly, Katharine Hsu (International Journal of Telerehabilitation, 2013)
The Mid-Atlantic Resource Center (MATRC; http://www.matrc.org/) advances the adoption and utilization of telehealth within the MATRC region and works collaboratively with the other federally funded Telehealth Resource Centers to accomplish the same nationally. MATRC offers technical assistance and other resources within the following mid-Atlantic states: Delaware, District of Columbia, Kentucky, Maryland, North Carolina, Pennsylvania, Virginia and West Virginia. The 2014 MATRC Summit “Adding Value through Sustainable Telehealth” will be held March 30-April 1, 2014, at the Fredericksburg Expo & Conference Center, Fredericksburg, VA. The Summit will explore how telehealth adds value to patients, practitioners, hospitals, health systems, and other facilities. Participants will experience a highly interactive program built around the case history of “Mr. Doe” as he progresses through the primary care, inpatient hospitalization, and post-discharge environments. The Summit will conclude with a session on financial and business models for providing sustainable telehealth services. For further information and registration, visit: http://matrc.org/component/content/article/2-uncategorised/80-mid-atlantic-telehealth-resource-summit-2014